Commodified Empowerment in Ramadan Advertising: Mythological Women in Marjan Campaigns - Putranto, Rizky Bayu (Universitas Muhammdiyah Yogyakarta, 2026)
This study examines how female empowerment is represented in Marjan Ramadan advertisements through mythological narratives and how these representations relate to consumer culture. Using a qualitative approach, the study analyzes three Marjan Ramadan advertisements featuring Dewi Sri (2022), Putri Hijau (2024), and the daughter of Mpu Baradah in the Calon Arang narrative (2025). Data were collected from official advertisements and analyzed using Barthes’ semiotic framework and Derridean deconstruction, supported by feminist media perspectives. The findings show that the three female protagonists are consistently represented as central agents who confront threats, resolve conflicts, and restore environmental, social, or moral order. Through these mythological figures, female empowerment is constructed as leadership, protection, and collective responsibility. However, the analysis also reveals that empowerment is not presented as an autonomous outcome. In all three advertisements, conflict resolution is followed by communal consumption rituals centered on Marjan syrup, linking empowerment to consumption-oriented narratives. Consequently, empowerment operates within a dual framework: it appears progressive at the level of representation while remaining embedded within commercial logic at the structural level. The study concludes that Marjan advertisements transform female empowerment into a commodified discourse that connects gender representation, cultural symbolism, Ramadan values, and consumer practices.